Application-Specific Hardware Architecture Design with VHDL - Belean, Bogdan (Signals and Communication Technology,, 2018)
This book guides readers through the design of hardware architectures using VHDL for digital communication and image processing applications   that require performance computing. Further it includes the description of all the VHDL-related notions, such as language, levels of abstraction, combinational vs. sequential logic, structural and behavioral description, digital circuit design, and finite state machines. It also includes numerous examples to make the concepts presented in text more easily understandable.